Working Online During COVID-19: Accounts of First Year Students Experiences and Well-Being - Moosa, Moeniera; Bekker, Tanya (Frontiers in Psychology, 2022)
The sudden move to online learning due to the Covid-19 pandemic has created an influx of epistemological, psycho-social, emotional and financial challenges for first year students. Lecturers and academics had to find creative and sustainable ways of ensuring that all students were epistemologically included. New policies and practices were introduced rapidly at universities to facilitate the unavoidable move to online learning. As initial teacher educators at a public University in South Africa we noted that the sudden move to working online has presented various challenges to first year students’ overall well-being which has further exacerbated issues of exclusion and marginalisation for many. We argue that it is against this backdrop that this paper explores how the move to online learning has affected first year students’ overall well-being, at one teacher education institution. The Index for Inclusive Education was used as a theoretical lens to explore student’s perceptions of the institution’s policy, teaching and learning practices, and the institutional culture during this period. One hundred and eighty-seven purposively selected first year students participated in this qualitative, phenomenological research study. Data were collected by means of open-ended questionnaires. Responses were categorised by means of an emergent thematic analysis. The findings indicated that online learning compromised various aspects of well-being including physical, emotional, psycho-social and financial well-being for many students. The experiences of online learning and impact on well-being did however differ across students depending on their individual contexts and circumstances indicating that considerations of well-being need to take contextual realities into account to support the well-being and learning of all. We recommend that higher education institutions prioritise the psycho-social, emotional and financial well-being of students during the period of online learning and not just the pedagogic needs of the qualification.